2001
DOI: 10.1038/sj.bjp.0704054
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of annexin 1 in monocytic cells produces a high degree of spontaneous and stimulated apoptosis associated with caspase‐3 activation

Abstract: 1 Transfection of the pre-monomyelocytic U937 cell line with a plasmid coding for full-length annexin 1 (ANX1, 347 amino acid) leads to cell death by promoting apoptosis. In addition, overexpression of the N-terminal and the ®rst domain of the protein (144 amino acids, clone ANX1-S), which does not contain the Ca 2+ binding sites, gives susceptibility to cell apoptosis following activation by either 5 ng ml 71 tumour necrosis factor (TNF)-a or 1 ± 40 mg ml 71 etoposide. This was demonstrated by using the¯uores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
83
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 52 publications
4
83
1
1
Order By: Relevance
“…Recent studies have also shown that miRNA-196a levels are inversely correlated with survival in pancreatic adenocarcinoma patients (Bloomston et al, 2007). ANXA1 is known to be a mediator of apoptosis and suppressor of cell proliferation (Solito et al, 2001). By targeting and suppressing ANXA1 levels, miR-196a may promote deregulated growth characteristics in cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also shown that miRNA-196a levels are inversely correlated with survival in pancreatic adenocarcinoma patients (Bloomston et al, 2007). ANXA1 is known to be a mediator of apoptosis and suppressor of cell proliferation (Solito et al, 2001). By targeting and suppressing ANXA1 levels, miR-196a may promote deregulated growth characteristics in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ANXA1 overexpression promoted caspase-mediated apoptosis in bronchoalveolar cells (Debret et al, 2003) and macrophages (Solito et al, 2001) and facilitated H 2 O 2 -induced apoptosis in thymocytes (Sakamoto et al, 1996). In prostate cancer cell lines, ANXA1 overexpression resulted in reduced cell viability and colony formation, enhanced apoptosis and suppressed response to epidermal growth factor signaling (Hsiang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proteomic analysis revealed an elevated expression of this protein in treated HCT 116 cells as well. Several lines of evidence indicate that an overexpression of Annexin I induces caspase-3-mediated apoptosis in monocytic (24), bronchoalveolar (25), and prostate cancer cells (26), which again brings attention to the role of caspase-3-dependent apoptotic pathway in HCT 116. However, we cannot rule out the possibility that other apoptosis pathways are also provoked in this cell line, as we found activation of the AIF protein in treated cells, which provides direct evidence for induction of caspase-independent cell death process.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ANXA1 promotes apoptosis associated with caspase-3 activation (Solito et al, 2001). ANXA1 was identified as an 'eat-me' signal on apoptotic cells that are recognized and ingested by phagocytes (Arur et al, 2003).…”
mentioning
confidence: 99%